Molecular identification, biology and ecology of Titya synoecura (Dyar, 1914) (Lepidoptera: Lasiocampidae) in Panama - Santos Murgas, Alonso (2024)
This work provides information on molecular identification, biology and ecology of the moth Titya synoecura (Dyar, 1914) (Lepidoptera: Lasiocampidae) and aggregates of its larvae are recorded carrying out herbivory on Banara guianensis Aublet 1775 (Plantae: Salicaceae). Also, this species of moth is recorded for the first time in Panama. Information is provided on the behavior of the larvae in their nest, and information on their distribution in the region is updated.